Mangrove Oyster (Crassostrea belcheri) as a Biomonitor Species for Bioavailability of Polycyclic Aromatic Hydrocarbons (PAHs) from Sediment of the West Coast of Peninsular Malaysia - Vaezzadeh, Vahab; Zakaria, Mohamad Pauzi; Bong, Chui Wei; Masood, Najat; Mohsen Magam, Sami; Alkhadher, Sadeq (Taylor & Francis, 2019)
Rapid industrialization and urbanization in the west coast of Peninsular Malaysia has caused increasing pollution particularly of petroleum and petroleum by-products. Surface sediment and mangrove oyster (Crassostrea belcheri) were collected from five mangrove ecosystems in the west coast of Peninsular Malaysia and investigated for bioavailability of polycyclic aromatic hydrocarbons (PAHs). Sampling locations were selected from both remote areas with few or no previous records of petroleum pollution such as Pulau Merambong and polluted areas that are under international attention such as Klang mangrove ecosystem. PAH fractions were obtained through soxhlet extraction and two-step column chromatography and the fractions were injected to gas chromatography-mass spectrometry (GC-MS) for analysis. The concentrations of PAHs ranged from 151 to 4973 ng g−1 dw in the sediments, while from 309 to 2225 ng g−1 dw in the oysters. When tested for diagnostic ratios, a predominance of pyrogenic source PAHs was detected in the sediments, whereas PAHs in the oysters had mixed petrogenic and pyrogenic sources. A significant correlation (p < 0.05) was found between high molecular weight (HMW) PAHs in the sediments and oysters and biota accumulation factors (BAFs) of PAHs were approaching or exceeding unity indicating the ability of mangrove oyster in bioaccumulation of PAHs. Overall, this study indicates that mangrove oyster (C. belcheri) can be used as a biomonitor species for PAHs in an aquatic environment. © 2017, © 2017 Taylor & Francis Group, LLC.